Maslov index for heteroclinic orbits of non-Hamiltonian systems on a two-dimensional phase space - Xing, Qin (Topological Methods in Nonlinear Analysis, 2022)
Motivated by hu2019bifurcation and hu2017index, we use a geometric approach to define the Maslov index for heteroclinic orbits of non-Hamiltonian systems on a two-dimensional phase space, and we proceed by explaining the Maslov index is equal to the sum of the nullity of a family of Fredholm operators. As an application, we illustrate the role of our results in the Nagumo equation.